Quest for Citizenship: Examining the Interplay Between Legal Status and (Im)mobility Aspirations of Syrians in Turkey - Alahmad, Ziad; Çiçekli, Mehmet (Border Crossing, 2024)
(Im)mobility aspirations in onward migration is a growing area of study in forced migration that goes beyond the traditional understanding of forced migration patterns. It grants more agency to the individuals and views their movement as a non-linear, fragmented trip that changes based on a variety of factors. This paper contributes to this knowledge by providing evidence on the role of legal status on (im)mobility aspirations by examining the special case of Syrians in Turkey. The study utilizes correlation and regression analyses on a unique data set to analyze the relationship between (im)mobility aspirations and the various legal statuses Syrians in Turkey hold. The findings confirm correlation and causality between the two variables. In other words, the stronger the migrant’s legal status becomes the more mobility aspirations decrease and the other way round.